Comparative Study of Digital Marketing Communication Strategies of Somethinc, Scarlett Whitening, and Skintific Brands Through TikTok Live Streaming Media - Nifta Alifatul Khotijah; Andre Rohmanto; Ign. Agung Satyawan (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to analyze and compare digital marketing communication strategies used by Somethinc, Scarlett Whitening, and Skintific brands through TikTok Live. The research method used is a qualitative study by applying media content analysis methods using STP (Segmentation, Targeting, Positioning) and S-W-O-T (Strengths, Weaknesses, Opportunities, Threats) analysis. The research data was obtained through observation of content and interactions that occurred during live broadcasts on TikTok Live.which included digital media characteristics, convergence, and digital media elements. The results of this study show that the three brands have different approaches in their digital marketing strategies through TikTok Live. In this research, we compared digital marketing strategies between Somethinc, Scarlett, and Skintific brands through TikTok Live. The results showed that each brand has a unique approach in their digital marketing strategy through TikTok Live. In terms of segmentation factors, these three brands use different approaches. S-W-O-T analysis shows that each brand has its own strengths and weaknesses in their digital marketing strategy. The success of these brands in positioning themselves in the cosmetics industry through TikTok Live is heavily influenced by their ability to leverage internal strengths, overcome weaknesses, seize opportunities, and deal with existing threats.